Problematika Pembelajaran Yang Dihadapi Selama Pandemi Covid-19 - Putri Dwiyanti; Sujarwo Sujarwo (FKIP, Universitas Palangka Raya, 2023)
The purpose of this study is to identify related learning problems faced during the Covid-19 pandemic. The problem that occurs by some parties who feel this is certainly as a result of the enactment of distance learning from 2020 to the present. This research uses qualitative methods with data collection techniques through observation, interviews, documentation, and literature studies. The participants were 6 people, each consisting of students, teachers, and parents who felt the problem in the Jakarta area. The result of this study is that there are several learning problems faced during the Covid-19 pandemic in distance learning activities, namely the problem of students lacking facilities that can support the implementation of online learning, network constraints, conditions of the residential environment that are not conducive, limited students in understanding the material that has been given by teachers, and often experiencing saturation during learning activities. The problem of teachers is required to be able to adapt, not ready supporting facilities for teachers, limitations in controlling the classroom during learning activities, and the difficulty of teachers in providing assessments to students. Finally, parents are required to adapt and transform to online media used by schools, problems of daily busyness, and problems with student devices or communication tools to participate in learning activities